Cervical vertebrae affection in calcium pyrophosphate crystal deposition disease (description of a clinical case) - E. V. Cheremushkina; M. S. Eliseev; O. V. Zhelyabina (Современная ревматология)
Calcium pyrophosphate deposition disease (CPPD) is characterized by polymorphism of clinical manifestations: from asymptomatic course to severe chronic arthropathy with destruction of bone structures. It is believed that calcium pyrophosphate crystals are more often found in the knee and so-called root joints (hip and shoulder), as well as in the triangular fibro-cartilaginous complex. However, CPPD can also affect the axial skeleton. A pathological process localized in the spine is more common in older people and is rare at a young age. The article presents a case of chondrocalcinosis of the cervical spine in a 62-year-old female patient who did not have risk factors.